Deep brain stimulation targets for treating depression - Drobisz, Dominik; Damborská, Alena (Behavioural brain research, 2019)
Deep brain stimulation (DBS) is a new therapeutic approach for treatment-resistant depression (TRD). There is a preliminary evidence of the efficacy and safety of DBS for TRD in the subgenual anterior cingulate cortex, the ventral capsule/ventral striatum, the nucleus accumbens, the lateral habenula, the inferior thalamic peduncle, the medial forebrain bundle, and the bed nucleus of the stria terminalis. Optimal stimulation targets, however, have not yet been determined. Here we provide updated knowledge substantiating the suitability of each of the current and potential future DBS targets for treating depression. In this review, we discuss the future outlook for DBS treatment of depression in light of the fact that antidepressant effects of DBS can be achieved using different targets.
Keywords: Deep Brain Stimulation; hluboká mozková stimulace; Deep brain stimulation; Brain; zvířata; mozek; Humans; Major depressive disorder; depresivní poruchy; Depressive Disorder; lidé; Treatment-resistant depression; Animals